ADCP current measurements (600 kHz) on 09.03.2023 during RV HEINCKE cruise HE614 - Albinus, Michelle; Deyle, Lisa; Herold, Jens-Martin; Meyerjürgens, Jens; Wurl, Oliver; Badewien, Thomas Henry (PANGAEA, 2024)
Ocean velocities were collected by a Teledyne RD Instruments 600 kHz RiverRay ADCP that was mounted on an autonomous surface catamaran along a predefined transect pattern on March 09th 2023 during RV HEINCKE cruise HE614. The transducer was located at 0.257 m below the water line. The instrument was operated in single-ping, broadband mode with automatically selected bins (ranging from 0.1 - 0.8 m) depending on water depth and a blanking distance of 0.25 m. The catamaran's velocity was calculated from position fixes obtained by the Global Positioning System (GPS). Heading, pitch and roll data from the ADCP's internal gyrocompass and the navigation data were used by the data acquisition software ViSea DAS (AquaVision®) internally to convert ADCP velocities into earth coordinates. Accuracy of the ADCP velocities mainly depends on the quality of the position fixes and the catamaran's heading data.
Keywords: ADCP; current velocity; North Sea